تقریر ترمذی میں معاشرتی مسائل و معاملات کی شرح میں تقی عثمانی کا اسلوب: The Style of Taqi Usmani in the Explanation of Social Problems and Matters in Taqreer-e-Tirmizi - Dr. Shazia; Rabia Faryad; Nida Sharif (Al Manhal Research Journal, 2023)
“The human history is created and flourished by the tradition of moral glory, justice and kindness. This tradition belongs to the Quran and Hadiths. As the Quran is protected and safe, similarly, the followers and Sahaba of the Prophet Muhammad (PBUH) and different Muhaddith Imams have protected his sayings, actions and habits in the form of many collections. One of these collections is Jamia Tirmizi which is considered to be a very precious collection of hadiths. Many explanations of Jamia Tirmizi have been written, of which Taqreer-e-Tirmizi by Mufti Muhammad Taqi Usmani is a comprehensive and well-known explanation. This book explains many sharia commandments about social problems and matters such as kind relationship, severance of relations, murder, rape, Jihad, and clothing knowledge. Similarly, the importance of the sharia punishments, forced trade, and obedience of the ruler was addressed and many methods to improve the economic and social systems were mentioned. This study provides a brief picture of the procedures and styles adopted by Taqreer-e-Tirmizi which sheds light on the influence of Islamic rules and regulations in modern times.”